2017
DOI: 10.12669/pjms.333.12416
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns of clinical isolates of Pseudomonas aeruginosa isolated from patients of respiratory tract infections in a Tertiary Care Hospital, Peshawar

Abstract: Objective:This study aims to determine the prevalence and susceptibility pattern of Pseudomonas aeruginosa and multidrug-resistant (MDR) isolates in patients suffering from respiratory tract infection.Methods:A cross sectional study was conducted from January to December 2014 in Northwest General Hospital and Research Centre, Peshawar. A total of 615 sputum samples were collected from both in and out-patients. Sputum samples were collected as per standard procedure and were inoculated on Blood, MacConkey and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
21
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 12 publications
8
21
2
5
Order By: Relevance
“…Our data further suggested that the notable gram-negative bacteria, P. aeruginosa, Klebsiella and E. coli, having maximum resistance against antibiotics belonging to penicillin (amoxcillin) and cephalosporin (cefaclor, cefuroxime, ceftriaxone) classes, while antibiotics belonging to carbapenem (imipenem, meropenem), aminoglycosides (amikacin), quinolones (ofloxacin) and piptaz of penicillin class were among the most effective antibiotics against similar gram-negative bacteria. Similar to our findings, a study from Pakistan reported that the most frequent gram-negative isolate was P. aeruginosa (32.2%) followed by Klebsiella (16.5%) and E. coli (12.5%), while imipenem, meropenem and tazobactam were among the most effective antibiotics [40]. These data suggested that the irrational or misuse of antibiotics due to self-prescribing upon experiencing similar symptoms, non-adherence to standard treatment guidelines [19], [20], poor knowledge of clinician and the patient, and limited finances, could contribute to antimicrobial resistance towards the majority of first line and even the second line therapeutic options in various gram-negative URTP.…”
Section: Discussionsupporting
confidence: 91%
“…Our data further suggested that the notable gram-negative bacteria, P. aeruginosa, Klebsiella and E. coli, having maximum resistance against antibiotics belonging to penicillin (amoxcillin) and cephalosporin (cefaclor, cefuroxime, ceftriaxone) classes, while antibiotics belonging to carbapenem (imipenem, meropenem), aminoglycosides (amikacin), quinolones (ofloxacin) and piptaz of penicillin class were among the most effective antibiotics against similar gram-negative bacteria. Similar to our findings, a study from Pakistan reported that the most frequent gram-negative isolate was P. aeruginosa (32.2%) followed by Klebsiella (16.5%) and E. coli (12.5%), while imipenem, meropenem and tazobactam were among the most effective antibiotics [40]. These data suggested that the irrational or misuse of antibiotics due to self-prescribing upon experiencing similar symptoms, non-adherence to standard treatment guidelines [19], [20], poor knowledge of clinician and the patient, and limited finances, could contribute to antimicrobial resistance towards the majority of first line and even the second line therapeutic options in various gram-negative URTP.…”
Section: Discussionsupporting
confidence: 91%
“…In other studies, resistant isolates reached 47% in pediatrics ICUs from India 8 or 40% in strains recovered from respiratory samples in a hospital in Pakistan. 9 The increase of multiresistant strains in ICU-acquired infections suggests the existence of reservoirs that should be identified and eradicated. The clinical impact of multiresistance to anti-pseudomonal antimicrobial agents includes delay in the administration of appropriate treatment, longer ICU stay, more days on mechanical ventilation, and higher mortality.…”
Section: Design and Study Populationmentioning
confidence: 99%
“…Pseudomonas aeruginosa is an aerobic Gram-negative bacillus and an opportunistic pathogen that is abundant in various habitats. It has been implicated in different opportunistic infections and nosocomial outbreaks in human hospitals [ 21 ]. A large number of hospital outbreaks have been linked to environmental sources, particularly water systems [ 3 , 27 ].…”
mentioning
confidence: 99%
“…A large number of hospital outbreaks have been linked to environmental sources, particularly water systems [ 3 , 27 ]. The species can evidently rapidly acquire resistance to various antimicrobial agents, and is capable of forming a biofilm [ 18 , 21 ], which acts as a direct barrier to phagocytic cells and offers innate resistance to antibiotics and disinfectants [ 10 ]. Most P. aeruginosa infections are difficult to treat because of the pathogen’s ability to resist many structurally unrelated antibiotics via both intrinsic and acquired antibiotic resistance mechanisms [ 13 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation